2018
DOI: 10.1186/s13063-017-2414-5
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation using low-level laser therapy (LLLT) for patients with chronic traumatic brain injury: a randomized controlled trial study protocol

Abstract: BackgroundPhotobiomodulation using low-level laser therapy (LLLT) has been tested as a new technique to optimize recovery of patients with traumatic brain injury (TBI). The aim of this study is to evaluate inhibitory attentional control after 18 sessions of active LLLT and compare with the placebo group (sham LLLT). Our exploratory analysis will evaluate the efficacy of the active LLLT on verbal and visuospatial episodic memory, executive functions (working memory, verbal and visuospatial fluency, attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 59 publications
1
16
0
1
Order By: Relevance
“…Different studies have suggested a positive effect of PBM treatment in TBI patients ( Naeser et al, 2014 ; Poiani et al, 2018 ; Carneiro et al, 2019 ). NIR between 700–1000 nm readily penetrates the scalp and skull and has the potential to improve cellular activity of compromised brain tissue ( Santos et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have suggested a positive effect of PBM treatment in TBI patients ( Naeser et al, 2014 ; Poiani et al, 2018 ; Carneiro et al, 2019 ). NIR between 700–1000 nm readily penetrates the scalp and skull and has the potential to improve cellular activity of compromised brain tissue ( Santos et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NIR between 700–1000 nm readily penetrates the scalp and skull and has the potential to improve cellular activity of compromised brain tissue ( Santos et al, 2018 ). Most studies employing NIR treatment have focused on evaluating the efficacy of this exposure on neuropsychological defects like impaired cognition and mood arising from brain injury ( Poiani et al, 2018 ; Santos et al, 2018 ) but none have looked at the effect of NIR on gene transcription. Since failing mitochondria can place the cell in energy crisis, mitochondrial dysfunction after injury could affect gene transcription, an energy demanding process ( Muir et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poiani and colleagues report that a design of a randomized double-blinded trial of photobiomodulation using low-level laser therapy (LLLT) could be an effective low-cost treatment for patients with traumatic brain injury (TBI). The results were evaluated to see whether LLLT could improve or restore cognitive sequel after TBI [49]. Santos et al published a design of a double-blinded, randomized, controlled trial of patients with diffuse axonal injury due to a severe TBI in an acute stage.…”
Section: Neurostimulation/neuromodulation and The Brain-computer Intementioning
confidence: 99%
“…Regarding treatment, peripheral treatment (e.g., physical therapy, speech therapy), pharmacological (i.e., amantadine, zolpidem) and nonpharmacological interventions (i.e., deep brain stimulation, spinal cord Stimulation) have been investigated in the last decade, however, there remain few effective therapies for patients with DOCs (Schiff et al, 2007;Della Pepa et al, 2013;Angelakis et al, 2014;Cossu, 2014;Tucker and Sandhu, 2016). Current evidence suggests that non-invasive brain stimulation (NIBS) including transcranial direct current stimulation (tDCS), Transcranial magnetic stimulation (TMS), and low-level laser therapy (LLLT), seems to be promising treatments (Thibaut et al, 2014;Xia et al, 2017;Poiani et al, 2018;Huang et al, 2019). For instance, Xia et al (2017) reported that 10 Hz multisession repetitive TMS applied to the left dorsolateral prefrontal cortex (DLPFC) has a potential benefit for the rehabilitation of patients with severe DOC, with an increase in CRS-R total scores in 5 out 5 MCS patients and 4 out of 11 VS/UWS patients after 30-day treatment.…”
Section: Introductionmentioning
confidence: 99%